The effective of syntax in semantic: cases in Arabic grammar - Yaacob, Solehah@Nik Najah Fadilah; Yaacob, Adli (IACSIT Press, 2014)
The research studies the role of the Grammatical Government in interpreting Vowel and Semantic Changes in Arabic grammar in explaining the semantic changes resulting from phonetic changes, especially in respect to vowels. In order to signify the changing of vowel, the role of grammatical government will be accounted based on some cases in Arabic grammar.